Understanding Ki Hadjar Dewantara’s educational philosophy - I Putu Ayub Darmawan; Edi Sujoko (International Journal of Humanities and Innovation (IJHI), 2019)
This article aims to describe the philosophy proposed by Ki Hadjar Dewantara ing ngarsa sung tuladha, ing madya mangun karsa, tut wuri handayani interpreted using Schleiermacher’s hermeneutics. By doing grammatical and psychological interpretation, the authors explored issues on understanding how the philosophy affected Ki Hadjar Dewantara’s life. It was done by apprehending the background condition, which inspired his vision, thinking framework, and other related thinking concept. Ki Hadjar Dewantara’s vision is an educational concept, which implements local wisdom in the middle of the harsh life of colonialism. The philosophy of Ki Hadjar Dewantara comes from the meaningful local wisdom that both teacher and leader should be in the front performing model or example, in the middle to build intention, and behind to motivate learners/public.